Effect of electrolytes on electrochromic properties and morphology of poly(2,5-dimethoxy aniline) films - Bureerat Suephatthima (2018)
Poly(2,5-dimethoxyaniline) (PDMA) was electrochemically synthesized in oxalic (H < inf > 2 < /inf > C < inf > 2 < /inf > O < inf > 4 < /inf > ) nitric (HNO < inf > 3 < /inf > ) and hydrochloric (HCl) acids and deposited onto flexible indium tin oxide at various synthesis times and deposition potentials as electrochromic materials. The PDMA films were characterized by FT-IR-spectrometry, scanning electron microscopy, UV-Vis spectrophotometry and cyclic voltammetry. All PDMA films show reversible colour changes from yellow to green corresponding to the transition from the fully reduced state to the fully oxidized state under potential switching. The surface morphology and thickness of PDMA films depend critically on the type of acids used in the electrochemical polymerization process. The morphology of PDMA are highly porous microfibres (H < inf > 2 < /inf > C < inf > 2 < /inf > O < inf > 4 < /inf > and HNO < inf > 3 < /inf > ), tiny granular aggregate (HCl) and particle agglomerate depending on the polymerization time. The fastest response time observed via colour changing of 3.7 s is obtained from the HCl-PDMA film at 3.5 volt and at the synthesis time of 6 min, as primarily due to the thickness of the film. The flexible PDMA film is demonstrated here as a potential candidate to be used in electrochromic devices. © 2014 Indian Academy of Sciences.